Constitutional standards of protection of the life of the conceived child in the Polish legal order - Olszówka, Marcin; Zalewski, Bartosz (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
The chapter reconstructs the constitutional standard for protecting the life of a conceived child under Articles 1, 2, 18, 30, and 38 of the 1997 Polish Constitution, drawing on Constitutional Tribunal rulings, including those of 28 May 1997 (K 26/96) and 22 October 2020 (K 1/20), and relevant literature. The legislature's obligation to protect the life of a conceived child follows primarily from Article 30, requiring respect for inherent, inalienable human dignity as the source of all rights and freedoms; dignity attaches to man as a being of special ontological status arising from belonging to the human species. Article 38 guarantees legal protection of every human being's life, including the unborn, regardless of health or conception circumstances. Other provisions are subsidiary: Article 1 (common good), Article 2 (democratic rule of law), and Article 18 (protection of motherhood, a relationship established at karyogamy).